Odpowiedzi

2009-12-15T14:08:50+01:00
A)2x+7=19
2x = 19 - 7
2x = 12
b)-3x+1=11
-3x = 11-1
-3x=10
c)4x-17=0
4x = 0 + 17
4x = 17
d)5x+3=-12
5x = -12 -3
5x = -15
e)12x+7=9x+10
12x-9x = 10-7
3x = 3
f)8-2x=5x-5
8 +5 = 5x +2x
13 = 7x
g)3(x+2)+2(2x-3)=x-12
3x+6+4x-6 = x-12
3x+4x-x = -12
6x = -12
1 2 1
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-12-15T14:12:10+01:00
A) 2x=12
x=6
spr. 2*6+7=19
19=19
b) -3x=10
x=-3 1/3
spr.
-3*(-3 1/3)+1=11
10+1=11
11=11
c) 4x=17
x=4 1/4
spr. 4*4 1/4-17=0
17-17=0
0=0
d) 5x=-15
x=-3
5*(-3)+3=-12
-15+3=-12
-12=-12
e) 12x+7=9x+10
3x=3
x=1
f) 8-2x=5x-5
13=7x
x=1 6/7
g) 3(x+2)+2(2x-3)=x-12
3x+6+4x-6=x-12
7x=x-12
6x=-12
x=-2

1 1 1
2009-12-15T14:13:35+01:00
A)2x+7=19
2x=19-7
2x = 12//:2
x = 6


b)-3x+1=11
-3x = 11-1
-3x = 10 // :-3
x = - 3 i jedna trzecia

c)4x-17=0
4x= 0+17
4x = 17//:4
x= 4,25

d)5x+3=-12
5x= -12-3
5x = -15//:5
x=-3


e)12x+7=9x+10
12x-9x = 10-7
3x=3//:3
x=1



f)8-2x=5x-5
8+5=5x+2x
13=7x//:7
1 i jedna siódma = x


g)3(x+2)+2(2x-3)=x-12
3x+6+4x-6=x-12
7x=x-12//+x
8x=12//:8
x= 1,5


mam nadzieję że dasz naj;P